In‐Vitro Permeability of Neutral Polystyrene Particles via Buccal Mucosa. Issue 3 (30th October 2012) - Teubl, Birgit Johanna; Meindl, Claudia; Eitzlmayr, Andreas; Zimmer, Andreas; Fröhlich, Eleonore; Roblegg, Eva
Abstract Drugs can be absorbed well in the oral cavity, which eliminates problems related to intestinal and hepatic first‐pass metabolism. Although it is well‐established that nanoparticles are small enough to penetrate/permeate epithelial barriers, there is no clear understanding of how they interact with the buccal mucosa. This work provides useful information regarding particle properties with regard to mucosal uptake and can be used for the rational design of nanocarriers. In the buccal mucosa, the uptake of neutral polystyrene nanoparticles (PP) is size‐dependent. Compared to 25 and 50 nm particles, 200 nm PP particles penetrate into deeper regions of the mucosa. This is attributed to the structure of the buccal mucosa, i.e., mucus layer and microplicae. The particles permeate the mucus layer and deposit in ridge‐like folds of superficial buccal cells. Thus, the effects of thermodynamic driving forces and/or interparticle electrostatic repulsion are enhanced and cellular uptake might be reduced for smaller particle sizes.